Strategi Mengembangkan Talenta, Prestasi, dan Akhlak Mulia Siswa - Andrizal Andrizal; Suswati Hendriani; M. Haviz; Annisaul Khairat (ISLAMIKA, 2023)
The aim of this research is to find out what strategies are implemented by the leadership of Al-Mumtaz Islamic High School, Solok City in developing students' talents, achievements and noble morals. This research uses a qualitative field research approach, a case study approach. Research site at Al Muntaz Islamic High School, Solok City. The research informants were the school principal, committee chairman, deputy principal, Head of the Achievement Education and Training Center (PPLP), teachers, students and elements within the Al Muntaz High School School environment, Solok City. The instruments of this research are interviews, observation sheets and documentation studies. The data collection technique used was through in-depth interviews, role observation and documentation studies. The data technique is by triangulation, namely source triangulation and technical triangulation. The results of the research show that the strategies used by the Principal of Al Muntaz Islamic High School in developing students' talents, achievements and morals include developing students' potential according to their wishes, while to form morals, they are guided by the morals of the Prophet SAW in everyday life and then doing everything in earnest.